Drug-induced toxic Myocarditis: Doxorubicin once again leading to Heart Failure - Nuno; Francisco Cunha (Sociedade Galega de Medicina Interna, 2016)
Treatment protocols in Oncology experienced massive changes in recent decades which have contributed to improve the morbidity and mortality of cancer. However, these advances were often achieved at the expense of significant side effects. The authors describe a case of a 62 year old woman with Follicular non-Hodgkin's Lymphoma who develops a toxic Myocarditis due to Doxorubicin. Anthracyclines cardiotoxicity is an established irreversible complication. There are a few measures that shall be taken into account in order to supervise, prevent and treat these patients.